Kinerja ekstrak bunga Plumeria acuminata kering pada anastesi ikan bandeng (Chanos chanos) - Taemnanu, Anika D; Lukas, Ade Yulita Hesti; Tobuku, Ridwan (Jurnal Aquatik, 2024)
This research aims to determine the effect of extracts from frangipani flowers under anesthesia during dry transportation on the growth of milkfish and their survival. In the research, fish measuring 4-6 cm and weighing 4-5g were used. The test fish were fasted for 3 days to reduce metabolic activity before being transported. Before packing, a treatment solution is made according to the concentration, namely 4 mg/L, 6 mg/L, and 8 mg/L. Test fish that are placed in the treatment solution are observed for the time required during the fermentation process. Fish that have been knocked out are placed in a transportation container in the form of low-temperature sawdust and lined with gauze and ice. The test fish were then transported for 12 hours and the fish were placed back in a container containing clean aura. The number of fish that died for each treatment was recorded. The method used was a completely randomized design (CRD), where there were 3 treatments with repetition 3 times. The variables measured were the duration of the stunning process, sedative time and survival time. The research results showed that the higher the concentration of dried Plumeria acuminata extract, the higher the sedative time but the lower the stunning time. Apart from that, the results of this research also show that the higher the concentration of Plumeria acuminata extract is followed by the higher the survival rate. Keywords: Plumeria acuminata flowers, extract, survival time, sedative time, sedative time